Embryonic Programs in Cancer and Metastasis—Insights From the Mammary Gland - Lee, May Yin (Frontiers in Cell and Developmental Biology, 2022)
Cancer is characterized as a reversion of a differentiated cell to a primitive cell state that recapitulates, in many aspects, features of embryonic cells. This review explores the current knowledge of developmental mechanisms that are essential for embryonic mouse mammary gland development, with a particular focus on genes and signaling pathway components that are essential for the induction, morphogenesis, and lineage specification of the mammary gland. The roles of these same genes and signaling pathways in mammary gland or breast tumorigenesis and metastasis are then summarized. Strikingly, key embryonic developmental pathways are often reactivated or dysregulated during tumorigenesis and metastasis in processes such as aberrant proliferation, epithelial-to-mesenchymal transition (EMT), and stem cell potency which affects cellular lineage hierarchy. These observations are in line with findings from recent studies using lineage tracing as well as bulk- and single-cell transcriptomics that have uncovered features of embryonic cells in cancer and metastasis through the identification of cell types, cell states and characterization of their dynamic changes. Given the many overlapping features and similarities of the molecular signatures of normal development and cancer, embryonic molecular signatures could be useful prognostic markers for cancer. In this way, the study of embryonic development will continue to complement the understanding of the mechanisms of cancer and aid in the discovery of novel therapeutic targets and strategies.